Role of Maize Weevil, Sitophilus zeamais Motsch. on Spread of Aspergillus section flavi in Different Nepalese Maize Varieties - K. Bhusal; D. Khanal (Advances in Agriculture)
Experiments were conducted to find out the role of maize weevil, Sitophilus zeamais Motsch. on spread of green fungus, Aspergillus section flavi, in different varieties of stored maize in laboratory in 2016. Lab experiment was conducted to find the role of weevil on spread of A. flavus on five main varieties of maize grown at Nepal in split plot design, namely, Arun-2, Arun-4, Manakamana-1, Manakamana-3, and Rampur composite with three replications at NAST, Khumaltar, from August to September 2016. One hundred grams of each maize variety was exposed to weevil along with fungus and with fungus only to see the spread of the fungus under presence and absence of weevil. Among the tested five maize varieties, the lowest infestation was observed on Rampur Composite (14.99%) while it was the highest on Manakamana-3 (87.70%). The highest mean infestation (75.58%) was found under weevil released condition while it was lower (62.16%) under nonreleased condition. In presence of weevil, the infestation of the fungus increased and in their absence the infestation was low which signifies the role of weevil in fungal spread. All indices indicate that Rampur composite is the best variety among the five tested varieties in terms of storage under the presence of fungus and weevils. This study also indicates ample scope for further study on different varieties of maize under several storage conditions.